2019
DOI: 10.1111/jpi.12584
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin alleviates cognition impairment by antagonizing brain insulin resistance in aged rats fed a high‐fat diet

Abstract: Brain insulin resistance, induced by neuroinflammation and oxidative stress, contributes to neurodegeneration, that is, processes that are associated with Aβ accumulation and TAU hyperphosphorylation. Here, we tested the effect of chronic administration of melatonin (MLT) on brain insulin resistance and cognition deficits caused by a high-fat diet (HFD) in aged rats. Results showed that MLT supplementation attenuated peripheral insulin resistance and lowered hippocampal oxidative stress levels.Activated microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 89 publications
(128 reference statements)
1
52
0
1
Order By: Relevance
“…Previous researches have showed that melatonin has a beneficial effect on gut, brain, and liver function, such as alleviating cognition impairment by antagonizing brain insulin resistance in aged rats fed a high-fat diet [ 31 ], enhancing neural stem cell differentiation and engraftment [ 74 ], protecting against lipid-induced mitochondrial dysfunction [ 75 ], and alleviating cadmium-induced liver injury [ 76 ]. These effects were achieved by varieties of molecular pathways including differentiation, oxidative stress, immune function, and apoptosis [ 77 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches have showed that melatonin has a beneficial effect on gut, brain, and liver function, such as alleviating cognition impairment by antagonizing brain insulin resistance in aged rats fed a high-fat diet [ 31 ], enhancing neural stem cell differentiation and engraftment [ 74 ], protecting against lipid-induced mitochondrial dysfunction [ 75 ], and alleviating cadmium-induced liver injury [ 76 ]. These effects were achieved by varieties of molecular pathways including differentiation, oxidative stress, immune function, and apoptosis [ 77 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, astrocytes and microglia in the hippocampus were activated induced by LPS invasion [ 84 , 85 ]. Subsequently, inflammation-related cytokines, such as TNF- α and IL-1 β , were increased in the hippocampus as well as the nuclear factor kappa-B (NF- κ B) pathway [ 31 , 84 , 85 ]. How LPS invaded the brain?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with type 2 diabetes mellitus (T2DM) have a lower nocturnal melatonin production compared to ones without diabetes [62]. Several studies indicated that single dose of melatonin in healthy post-menopausal and pre-menopausal women (1 mg and 5 mg respectively) worsens the glucose tolerance test in the morning and the evening [63,64]. On the other hand, chronic treatment with prolonged-release melatonin (2 mg) over a 5-month period decreases the level of HbA1c and betters glycemic control [65].…”
Section: Anti-diabetic Effects Of Melatoninmentioning
confidence: 99%
“…Increased neuroinflammation is also involved in the initiation and progression of NDDs such as AD and PD. Melatonin could inhibit the activation of microglia and astrocytes [ 256 , 257 ], suppress activation of nuclear factor-κB (NF-κB), a critical transcription factor for many pro-inflammatory cytokines and chemokines, and thus attenuate the inflammatory process [ 258 ]. The basal level of the inflammatory response in the aging brain is continuously activated, but its ability to respond to acute inflammatory stress is decreased.…”
Section: Translational Applications Of Melatonin Against Nddsmentioning
confidence: 99%